Variable trust in public health messaging during the first year of the COVID-19 pandemic in Southeast Alaska - van Doren, Taylor P.; Brown, Ryan A.; Izenberg, Max; Heintz, Ron; Simmons, Callie; Paddock, Raymond (Frontiers in Communication, 2023)
Public health messaging in the United States during the COVID-19 pandemic has been variable in effectiveness. Different levels of governmental institutions have different goals and methods; it is unclear how messaging from these disparate levels are received, trusted, and implemented. We investigate the degrees of trust of Alaska Native and non-Alaska Native people in Southeast Alaska for the U.S. federal, Alaska state, and local Southeast Alaskan governments to parse how Southeast Alaskans feel about relative preparation, actions, and public health messaging. We use data collected in two waves of a large regional survey: the first in April-June 2020, and the second in November 2020-February 2021. Results indicate that trust in the federal government was significantly lower than in the Alaska state government for each time period, and trust in both federal and state government significantly decreased between the two periods. Trust in the local governments of Southeast Alaska were significantly higher than both state and federal levels, and increased between the two survey waves, albeit insignificantly. We discuss potential drivers of these observations and outline how this can be leveraged for more comprehensive research into how relatively small communities with a large Native presence perceive public health messaging from different sources.